STUDIES ON PHYSICAL PROPERTIES OF CERVICAL MUCUS OF REPEAT BREEDING CROSSBRED COWS - ZAMAN, MALIK IMRANUL; SHARMA, UTSAV; KUMAR, SUDHIR; KUMAR, SHARAD (The Indian Journal of Animal Reproduction, 2023)
The examination of physical properties of cervical mucus in majority of the repeat breeding cows showed that the colour was turbid (64.44%), consistency was thick (84.44%), elasticity was elastic (62.22%) and fern pattern was typical (60.00% ). The pH value of cervical mucus in repeat breeding (7 .95 ± 0.096) cows was significantly (p<0.01) higher than the normal (7.35 ± 0.167) cows. The conception rate of 90.00 % was recorded in normal cows and 100.00% pregnancy rate was observed in clean, thin, elastic and typical fern pattern type of cervical mucus.